Penerapan Model Pembelajaran Kooperatif Tipe Make A Match Untuk Meningkatkan Hasil Belajar Siswa Pada Muatan IPS di Kelas IV - Djabba, Rasmi; Halik, Abdul; Amran, Muhammad; Firdasari, Firdasari (Universitas Negeri Makassar, 2023)
The problem in this research is the low learning outcomes in fourth grade students. The problem in this research is how the process of applying the make a match type of cooperative learning models in the students learning process on social studies content about economic activites in class IV UPT SD Negeri 4 Pinrang distric and wheather the application of the make a match type of cooperative learning model can improve students learning outcomes in social studies content on economic activities in class IV UPT SD Negeri 4 Pinrang Distric. Cycles I the research result on the learning process were in good qualification and the learning test result were in sufficient qualification. In the second cyclesthe research result on the learning process were in good qualification and the learning test result were in good qualification.